Prediction of injury risk in Chinese mine rescuers based on single factors and different threshold combinations of FMS and YBT - Yang, Guanghao; Gao, Di; Yang, Sanjun (Frontiers in Public Health, 2025)
PurposeThis study aims to investigate the correlation between FMS and YBT indicators with injuries and to explore a single predictive threshold or combinations of thresholds for practical reference.MethodsInjury histories of 96 Datong rescue team members were collected via questionnaire, and multiple FMS and YBT indicators were assessed at the same site on different occasions. Data were organized and categorized using Excel and SPSS 29.0. Threshold values derived from relevant literature on comparable occupational groups adopted as reference standards, and statistical analyses (t-test, chi-square) were applied to examine the associations between functional indicators and injury, and to evaluate the validity of both individual and combined threshold criteria.Results(1) Injuries primarily concentrated in the lumbar and knee regions, accounting for approximately 50% of total injuries. (2) There were highly significant differences between injured and uninjured groups in FMS scores and YBT bilateral reach distance difference (p < 0.01), as well as significant differences in YBT overall score (p < 0.05). (3) The injury rate was 76.8% when FMS score < 15, 80% when the YBT lower limb overall score < 95, and 89.39% when the bilateral reach distance difference > 4 cm. (4) When combining the criteria of FMS overall score < 15 and YBT bilateral reach distance difference > 4 cm, the injury rate increased to 90.38%.Conclusion(1) The threshold values for the overall scores of FMS and YBT can effectively predict injury risk. In contrast, the YBT bilateral reach distance difference demonstrates superior advantages. (2) The accuracy of combined predictions is higher, with the combination of an FMS 15 and YBT bilateral difference of 4 cm serving as the optimal standard.